2012
DOI: 10.1183/09031936.00027212
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of tiotropiumversussalmeterol: the POET-COPD trial

Abstract: The aim of this study was to perform a 1-yr trial-based cost-effectiveness analysis (CEA) of tiotropium versus salmeterol followed by a 5-yr model-based CEA.The within-trial CEA, including 7,250 patients with moderate to very severe chronic obstructive pulmonary disease (COPD), was performed alongside the 1-yr international randomised controlled Prevention of Exacerbations with Tiotropium (POET)-COPD trial comparing tiotropium with salmeterol regarding the effect on exacerbations. Main end-points of the trial-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Tiotropium + UC2. UCEngland: +£796 (€917)Belgium: +€969(2011)England: +0.051 QALYsBelgium: +0.052 QALYsEngland: £15,567 (€17,936) /QALYBelgium: €18,617/QALYAdding tiotropium to UC is cost effective94Hoogendoorn et al 2013 (Germany) [17]Alongside 1-year RCT + 5-year model (CUA)1 and 5 yearsBoehringer Ingelheim1. Tiotropium2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tiotropium + UC2. UCEngland: +£796 (€917)Belgium: +€969(2011)England: +0.051 QALYsBelgium: +0.052 QALYsEngland: £15,567 (€17,936) /QALYBelgium: €18,617/QALYAdding tiotropium to UC is cost effective94Hoogendoorn et al 2013 (Germany) [17]Alongside 1-year RCT + 5-year model (CUA)1 and 5 yearsBoehringer Ingelheim1. Tiotropium2.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining study reported higher QALY gains (0.42) [14]; however, the authors assumed an additional positive effect of tiotropium on cardiovascular outcomes (myocardial infarction, congestive heart failure) and used mapping to convert St George’s Respiratory Questionnaire (SGRQ) scores into utilities. One study compared tiotropium versus salmeterol based on the head-to-head POET-COPD clinical trial [17]. In this economic evaluation, 1-year trial-based cost effectiveness as well as model-based cost-effectiveness estimates (over 1-year and 5-year time horizons) were reported from both the societal and the payer’s perspective.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Für die Einordnung der Ergebnisse bezogen auf andere medikamentöse Therapieoptionen in Deutschland kann eine aktuell publizierte Kosten-Effektivitäts-analyse für LAMA (Tiotropium) versus LABA (Salmeterol) basierend auf den Daten der POET-Studie herangezogen werden. Die Modell-Berechnungen kommen mit 1961 € pro vermiedener Exazerbation aus Perspektive der GKV zu einem vergleichbaren Ergebnis (1852 €) [18]. Die Kosten pro gewonnenem QALY aus Sicht der GKV liegen bei der alleinigen Therapie mit Tiotropium niedrigerer (3488 €) als bei den Modellberechnungen für Roflumilast + LABA (19 457 €).…”
Section: Inputparameterunclassified